Characterization of the complete chloroplast genome of the Phoebe bournei - Beibei Chen; Yong Zeng; Chunlin Li; Bing Xu; Chuan Zhang; Wei Chen; Shuanglong Li; Weiyi Liu (Mitochondrial DNA. Part B. Resources, 2020)
Phoebe bournei is an endangered Lauraceae species in the world. In this study, the complete chloroplast genome sequence of Phoebe bournei was characterized. Its chloroplast genome size has 152,860 bp, containing a large single copy region of 93,778 bp, a small single copy region of 18,936 bp and a pair of IR regions of 20,073 bp. The overall GC contents of the chloroplast genome sequence was 39.1%. This circular genome contains 127 annotated genes, including 83 PCGs, 36 tRNAs and 8 rRNAs. The phylogenetic tree analysis result showed that Phoebe bournei was the closest relationship with Phoebe chekiangensis using the maximum likelihood (ML) method. This complete chloroplast genomes can be used for the forestry development of this valuable species in the future.